2017
DOI: 10.1002/hbm.23549
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain segmentation using inter‐subject correlation in fMRI

Abstract: The human brain continuously processes massive amounts of rich sensory information. To better understand such highly complex brain processes, modern neuroimaging studies are increasingly utilizing experimental setups that better mimic daily-life situations. A new exploratory data-analysis approach, functional segmentation inter-subject correlation analysis (FuSeISC), was proposed to facilitate the analysis of functional magnetic resonance (fMRI) data sets collected in these experiments. The method provides a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 68 publications
1
18
1
Order By: Relevance
“…The time course of each IC can then be examined and related to the paradigm . Second, if the ISC analysis identifies a large number of regions surviving a particular statistical criterion, one can submit the average time courses throughout the brain to a clustering algorithm to functionally parcellate the cortex or identify ROIs with similar time series (Kauppi et al, 2010b(Kauppi et al, , 2017Thomas et al, 2018). Alternatively, ISC can be computed using a sliding-window approach in order to identify epochs in which ISC was highest, which can then be related to the stimulus (window sizes in the literature range from 10 to 60 TRs; Nummenmaa et al, 2012;Simony et al, 2016).…”
Section: Interpreting Isc Resultsmentioning
confidence: 99%
“…The time course of each IC can then be examined and related to the paradigm . Second, if the ISC analysis identifies a large number of regions surviving a particular statistical criterion, one can submit the average time courses throughout the brain to a clustering algorithm to functionally parcellate the cortex or identify ROIs with similar time series (Kauppi et al, 2010b(Kauppi et al, , 2017Thomas et al, 2018). Alternatively, ISC can be computed using a sliding-window approach in order to identify epochs in which ISC was highest, which can then be related to the stimulus (window sizes in the literature range from 10 to 60 TRs; Nummenmaa et al, 2012;Simony et al, 2016).…”
Section: Interpreting Isc Resultsmentioning
confidence: 99%
“…J€ a€ askel€ ainen et al, 2008;Golland et al, 2007;Kauppi et al, 2010Kauppi et al, , 2017Nummenmaa et al, 2012;Lahnakoski et al, 2012). Compared with the strong across-viewers correlations in BOLD signals (up to 0.78 in Kauppi et al, 2010), the correspondingly calculated intersubject correlations of MEG or EEG signals are usually weaker (typically less than 0.1) both at sensor (Bridwell et al, 2015) and source level (Suppanen, 2014;Chang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While Chen et al (2016) demonstrated the importance of subject-wise rather than element-wise permutations in ISC group comparisons, they based their analysis on simple, purely synthetic data. However, in ISC analysis, this kind of synthetic data fails to reproduce some of the main characteristics of ISCs seen in actual fMRI experiments such as the increase of variance of subject-pair-wise ISCs with the increase of mean ISCs (Kauppi et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…This is a biased variance estimate as it does not account for the dependencies between the elements of the correlation matrix z (i) j (n, m). On the other hand, it is an approximation, up to a multiplication by a constant, of the leave-one-subject-out variance defined by Kauppi et al (2017). We definev…”
mentioning
confidence: 99%